Research on collision detection method and response strategy for Delta robots - Mei, Jiangping; Ning, Puxuan; Duan, Yunrui; Wei, Tianlin; Su, Xiaochen (Industrial robot, 2025)
Purpose The safety performance of Delta robots is particularly important. Hence, this paper aims to improve the existing method to achieve efficient and safe robots. Design/methodology/approach This paper designs a generalized momentum extended state observer method to estimate external torque. Meanwhile, a dynamic threshold method for current torque is designed. In addition, a segmented safety response strategy based on task space position feedforward is introduced. Findings Simulation and experimental results verify the effectiveness of the proposed method. Originality/value This paper designs a dynamic threshold collision detection method that does not require external sensors. Compared with static threshold collision detection methods, this method can avoid false alarm problems. This paper also proposes a segmented safety response strategy, which can improve the efficiency and safety of Delta robots.